(untitled) (Journal of Monno Medical College, 2024)
Background: Cervical cancer is the most destabilizing cancer that grows increasingly prevalent worldwide. The Southeast Asia region has the greatest incidence and mortality rates due to widespread use of smokeless tobacco (SLT) products, a lack of screening programmes, and immunization against cervical cancer. Objective: To assess the association between smokeless tobacco consumption and carcinoma of cervix. Methodology: A case-control study was conducted with 272 women aged 18-49 years, conveniently selected from both outpatient and inpatient settings at the National Institute of Cancer Research and Hospital (NICRH) in Dhaka, Bangladesh. The selection of NICRH was purposive. Participants underwent interviews using a pre-tested, semi-structured questionnaire between January and December 2019. Results: The mean age of cases was 49.8±8.8 years, while the mean age of controls was 48.5±9.3 years. In comparison to controls (52.2%), the majority of patients (65.4%) consumed SLT throughout their entire lives. A significant relationship was found between SLT use and the development of cervical cancer (p<0.05). Those who have consumed any SLT in their lives are 1.7 times more likely to develop cervical cancer than those who have not taken any SLT. Cases (22.8%) used betel quid with jorda >5 times, compared to controls (14.7%), and intensity of Gul used ≤5 among cases (9.6%) than controls (2.9%). Compared to controls (56.3%), the majority of cases (76.4%) had been using SLT for more than 10 years, with a statistically significant difference (p<0.05). Cases used SLT for a longer time (19.2±10.3) compared to controls (15.6±11.1), with a significant association (p<0.05). Conclusion: The study revealed a significant association between the risk of cervical cancer and the extent and duration of exposure to SLT. To minimize the risk of cervical cancer, contemplate restricting SLT production and utilization. Journal of Monno Medical College June, 2024; 10 (1):17-22